2008
DOI: 10.1590/s1413-86702008000500016
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal acquired toxoplasmosis patients in an infectious diseases reference center

Abstract: Infection caused by Toxoplasma gondii, toxoplasmosis, is one of the most frequent zoonoses in the world; it normally affects both genders equally. Humans are one of several possible intermediate hosts, and the disease is oligosymptomatic in most cases. Vertical transmission is an important cause of fetal malformation and sequels in newborns. Approximately 10% of postnatal cases present multiple manifestations, ranging from low fever and mild lymphadenopathy to severe encephalitis. In moderate cases, lesions su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 29 publications
1
13
0
Order By: Relevance
“…7 In pediatric patients, however, the relationship between PAN and infection is not clear. 8 While the present patient was being investigated for prolonged fever, high antibody titers were observed for Toxoplasma gondii infection, and also the Sabin Feldman test supported the diagnosis. This patient's toxoplasmosis occurred at the onset of PAN symptoms (fever, myalgia, rash).…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…7 In pediatric patients, however, the relationship between PAN and infection is not clear. 8 While the present patient was being investigated for prolonged fever, high antibody titers were observed for Toxoplasma gondii infection, and also the Sabin Feldman test supported the diagnosis. This patient's toxoplasmosis occurred at the onset of PAN symptoms (fever, myalgia, rash).…”
Section: Discussionsupporting
confidence: 63%
“…With regard to acute toxoplasmosis infection, myalgia can also be seen in up to 8% of patients but the present patient's myalgia seems unlikely to be explained by only Toxoplasma infection because he had other symptoms. 8 RCA RCA Fig. 1 (a)…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, interpretation of the increased IgM seroprevalence should be taken with care since tests for detection of IgM antibodies may have a high rate of false positive results caused by limitations in test specificity or persistence of IgM antibodies [19]. Some known clinical features of toxoplasmosis including visual impairment and headaches [2,20-22] were observed in some migrant workers. In fact, frequent headaches showed a borderline ( P  = 0.05) association with T. gondii seropositivity.…”
Section: Discussionmentioning
confidence: 99%
“…[68][69][70] A high prevalence, 80%, of ocular toxoplasmosis has been found in newborns with congenital toxoplasmosis in Brazil, 71 and a study from Rio de Janeiro found that 3% of acutely infected adults had chorioretinitis within 2 years of infection. 72 A higher prevalence of congenital toxoplasmosis has been found in Brazil compared to Europe followed by a higher rate of chorioretinitis in newborns and a higher rate of ocular disease in Brazilian infants after birth compared to European infants. 73 Severe, disseminated T. gondii infection with multiorgan involvement, including eye symptoms.…”
Section: South America and Central Americamentioning
confidence: 99%